Perceptions of students regarding the use of blackboard in an extended curriculum programme for teaching and learning : a social realist case study at a rural university in the Eastern Cape Province - Funda, Vusumzi; Kavi, Bongiwe; Ndlovu, Nomusa; Mpongwana, Konaye M.; Oluwatosin, Bamigboye (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
In today’s digital age, the importance of technology integration in educational systems has increased, with blackboard being one of the learning management systems used. Blackboard plays a vital role in teaching and learning for skill acquisition worldwide. The aim of this study is to ascertain the perceptions of extended curriculum programs students on the use of blackboard for teaching and learning. Therefore, the methodology adopted qualitative approach which involved interviewing Extended Curriculum Program students who are in their final year under the ECP. The study further involved 2 focus groups, 12 final year students from Alice campus and 12 final year students from East London campus, making it a sample population of 24 ECP final year students for data collection. However, the data collected was analyzed using thematic analysis with NVivo software. The results generated are challenges, general experiences, group collaboration, support and resource tools and technical issues which align with the institutional goals in pursuing high quality and innovative teaching and learning. The study findings indicate that ECP students perceive blackboard as a very important tool for teaching and learning as it offers flexibility, collaboration features and is easily accessible. However, they also highlighted technical issues, lack of engagement, not easy to use and inadequate training as challenges associated with the use of Blackboard and they suggested that there is need to improve strategies to foster inclusivity and participation. The relevance of this study was to have Extended Curriculum Program students’ opinion on the usability and effectiveness of Blackboard support for teaching and learning.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 8, Volume 9, 2025
Keywords: Students; Perceptions; Challenges; Blackboard; Extended Curriculum Programme; Learning management System; Blackboard systems (Computer programs); Computer-assisted instruction -- Computer programs; Education, Higher -- Computer-assisted instruction; Education higher, South Africa -- Eastern Cape; College students -- South Africa -- eastern Cape